Relationship Among Tau Antigens Isolated from Various Lines of Simian Virus 40-Transformed Cells - Simmons, Daniel T. (1980)
In addition to the virus-specified tumor antigens, simian virus 40-transformed cells contain at least one other protein which can be immunoprecipitated with serum from animals bearing simian virus 40-induced tumors. This protein, which is designated Tau antigen, has an apparent molecular weight of 56,000 as determined by electrophoresis on acrylamide gels. The relationship among Tau antigens isolated from different lines of simian virus 40-transformed cells was examined by comparing the methionine-labeled tryptic peptides of these proteins by two-dimensional fingerprinting on thin-layer cellulose plates. In this fashion, we initially determined that the Tau antigens isolated from three different lines of transformed mouse cells were very similar. Second, we found that Tau antigen isolated from a line of rat transformants was closely related, but not identical, to the mouse cell Tau antigens. Approximately 70% of their methionine peptides comigrated in two dimensions. Finally, we showed that Tau antigen isolated from a line of transformed human cells was only partially related to the mouse and rat proteins. About 40% of the methionine peptides of the human protein were also contained in the Tau antigens from the other two species. These results strongly indicate that the Tau antigens isolated from these various simian virus 40-transformed cell lines contain common amino acid sequences.